Amnion and chorion matrix maintain hMSC osteogenic response and enhance immunomodulatory and angiogenic potential in a mineralized collagen scaffold - Kolliopoulos, Vasiliki; Dewey, Marley J.; Polanek, Maxwell; Xu, Hui; Harley, Brendan A. C. (Frontiers in Bioengineering and Biotechnology, 2022)
Craniomaxillofacial (CMF) bone injuries present a major surgical challenge and cannot heal naturally due to their large size and complex topography. We are developing a mineralized collagen scaffold that mimics extracellular matrix (ECM) features of bone. These scaffolds induce in vitro human mesenchymal stem cell (hMSC) osteogenic differentiation and in vivo bone formation without the need for exogenous osteogenic supplements. Here, we seek to enhance pro-regenerative potential via inclusion of placental-derived products in the scaffold architecture. The amnion and chorion membranes are distinct components of the placenta that each have displayed anti-inflammatory, immunomodulatory, and osteogenic properties. While potentially a powerful modification to our mineralized collagen scaffolds, the route of inclusion (matrix-immobilized or soluble) is not well understood. Here we compare the effect of introducing amnion and chorion membrane matrix versus soluble extracts derived from these membranes into the collagen scaffolds on scaffold biophysical features and resultant hMSC osteogenic activity. While inclusion of amnion and chorion matrix into the scaffold microarchitecture during fabrication does not influence their porosity, it does influence compression properties. Incorporating soluble extracts from the amnion membrane into the scaffold post-fabrication induces the highest levels of hMSC metabolic activity and equivalent mineral deposition and elution of the osteoclast inhibitor osteoprotegerin (OPG) compared to the conventional mineralized collagen scaffolds. Mineralized collagen-amnion composite scaffolds elicited enhanced early stage osteogenic gene expression (BGLAP, BMP2), increased immunomodulatory gene expression (CCL2, HGF, MCSF) and increased angiogenic gene expression (ANGPT1, VEGFA) in hMSCs. Mineralized collagen-chorion composite scaffolds promoted immunomodulatory gene expression in hMSCs (CCL2, HGF, IL6) while unaffecting osteogenic gene expression. Together, these findings suggest that mineralized collagen scaffolds modified using matrix derived from amnion and chorion membranes represent a promising environment conducive to craniomaxillofacial bone repair.